Closing the gap? Results-based financing and socioeconomic-related inequalities in maternal health outcomes in Zimbabwe. - Makate, Marshall; Mahonye, Nyasha (Oxford University Press, 2024)
The results-based financing (RBF) program, first implemented in Zimbabwe in 2011 and gradually expanded to other districts, aimed to address disparities in maternal health outcomes by improving the utilisation of health services. This study leverages the staggered rollout of the program as a quasi-experimental design to assess its impact on asset wealth-related inequalities in selected maternal health outcomes. The objective is to determine whether RBF can effectively reduce these disparities and promote equitable healthcare access. We employ an extended two-way fixed effects (ETWFE) model to exploit temporal variation in RBF implementation as well as individual-level variation in birth timing for identification. Utilising pooled cross-sectional and nationally representative data from the Zimbabwe demographic and health surveys collected between 1999 and 2015, our analysis reveals significant reductions in relative and absolute maternal health inequalities, especially in the frequency and timing of prenatal care, delivery by caesarean section, and family planning. Specifically, the RBF program is associated with reductions in disparities for completing at least four or more prenatal care visits (-0.026, p < 0.01), first-trimester prenatal care (-0.033, p < 0.01), delivery by caesarean section (-0.028, p < 0.005), and family planning (-0.033, p < 0.005). Additionally, the program is associated with improved prenatal care quality, as evidenced by progress on the prenatal care quality index (-0.040, p < 0.01). These effects are more pronounced among lower socioeconomic groups in RBF districts, highlighting RBF's potential to promote equitable healthcare access. Our findings advocate for targeted policy interventions prioritising expanding access to critical maternal health services in underserved areas and incorporating equity-focused measures within RBF frameworks to ensure inclusive and effective healthcare delivery in Zimbabwe.